A. L. Lloyd and the English Folk Song Revival, 1934-44 - Gregory, E. David (The Canadian Society for Traditional Music / La Société canadienne pour les traditions musicales, 1997)
E. David Gregory outlines the genesis and contents of A.L. Lloyd's 194-4 history of English folk song, The Singing Englishman. Focusing on Lloyd's working-class childhood, subsequent jobs in Australia, London and Antarctica, contact with A.L. Morton, studies at the British Museum, leftist journalism, and BBC broadcasts, Gregory counters criticisms of Lloyd's writings by Maud Karpeles and Vic Gammon and demonstrates Lloyd's importance for the post-1945 Revival.